Fixed Point Theorems in Complex Valued B-Metric Spaces - Hasanah, Dahliatul (CAUCHY, 2017)
A complex-valued b-metric space is a generalization of a b-metric space in which its b-metric space has complex value. It can also be considered as a generalization of a complex-valued metric space. Hence, fixed point theorems that have been studied in b-metric spaces are now of interest whether the theorems are applicable in complex-valued b-metric spaces. In this paper we have obtained some fixed point theorems in complex-valued b-metric spaces. The theorems are derived from the corresponding theorems in b-metric spaces.